Prevention of endophthalmitis in cataract surgery: Integrative literature review - Fernandes, Ana Catarina Mattos; Maia, Camilla Castilho; Sobrinho, Edmundo Frota de Almeida (Seven Editora, 2024)
INTRODUCTION: Cataract is a disease that causes congenital or acquired opacity of the lens, which can cause partial or total loss of vision. Approximately 85% of cataracts are classified as senile, being considered the main causes of reduced vision in the world. The surgery for its correction consists of removing the opaque lens and replacing it with an intraocular lens (IOL). The most feared complication is postoperative endophthalmitis, which is an infectious condition caused by microorganisms introduced inside the eye during or after the surgical procedure. MATERIAL AND METHODS: This is a descriptive study of the Integrative Literature Review (RIL) type on the prevention and control of endophthalmitis after cataract surgeries. RESULTS: In this integrative literature review, 11 (eleven) articles that met the previously established inclusion criteria were analyzed. Most studies address the efficacy and recommendation of intracameral antibiotic use as the main prevention strategy for endophthalmitis in the postoperative period of cataracts. DOI:https://doi.org/10.56238/sevened2024.025-003